Graphene Oxide Nanosheets Retard Cellular Migration via Disruption of Actin Cytoskeleton. Issue 3 (20th October 2016) - Tian, Xin; Yang, Zaixing; Duan, Guangxin; Wu, Anqing; Gu, Zonglin; Zhang, Leili; Chen, Chunying; Chai, Zhifang; Ge, Cuicui; Zhou, Ruhong
Abstract : Graphene and graphene‐based nanomaterials are broadly used for various biomedical applications due to their unique physiochemical properties. However, how graphene‐based nanomaterials interact with biological systems has not been thoroughly studied. This study shows that graphene oxide (GO) nanosheets retard A549 lung carcinoma cell migration through nanosheet‐mediated disruption of intracellular actin filaments. After GO nanosheets treatment, A549 cells display slower migration and the structure of the intracellular actin filaments is dramatically changed. It is found that GO nanosheets are capable of absorbing large amount of actin and changing the secondary structures of actin monomers. Large‐scale all‐atom molecular dynamics simulations further reveal the interactions between GO nanosheets and actin filaments at molecular details. GO nanosheets can insert into the interstrand gap of actin tetramer (helical repeating unit of actin filament) and cause the separation of the tetramer which eventually leads to the disruption of actin filaments. These findings offer a novel mechanism of GO nanosheet induced biophysical responses and provide more insights into their potential for biomedical applications. Abstract : Graphene oxide (GO) nanosheets retard cell migration along with disruption of intracellular actin filaments. GO nanosheets exhibit strong binding capacity of actin monomers, leading to significant changes to their secondary structures. Simulation results show that GO nanosheets can insert into the interstrand gap of actin tetramer and broke the tetramer.